The RPUF Composite’s Physical and Mechanical Properties with Ramie Stem Particle Reinforcement - Stafian Nisa, Rihab; Dede Hermawan; Sasa Sofyan Munawar; Deni Purnomo; Bambang Subiyanto; Ismadi; Ahmad Syahrir; Fazhar Akbar (Talenta Publisher, 2024)
Rigid polyurethane foam (RPUF) is a common insulation material that has low thermal conductivity and good mechanical properties. The qualities of RPUF may be enhanced by adding natural fiber reinforcing. The purpose of this work is to examine how the mechanical and physical characteristics of RPUF composite are affected by the amount of ramie stem particles present. Japanese Industrial Standard (JIS) A 5908-2003 is the basis for the mechanical test (modulus of elasticity, modulus of rupture, compressive strength, internal bond) and the physical test (density, moisture content, water absorption). The study's findings suggest that the physical properties of the RPUF composite were affected by the addition of ramie particles for reinforcement. The density increase in particle content 2.5% – 7.5% range, is not statistically significant. The MC and WA increased statistically significantly. The values of MOE and MOR were not significantly different. In fact, with the addition of 2.5% and 5% ramie particles, the compressive strength value was higher than the RPUF composite without ramie particle filler. Then overall, the IB value was increased by increasing the ramie particles in the RPUF composite. The addition of 2.5-5% ramie particles into the RPUF composite showed optimum results in mechanical properties. Thereby, the addition of ramie particles in the RPUF composite means reducing the use of polyurethane. Therefore, it can reduce production costs. Then the product is more environmentally friendly